2012
DOI: 10.1121/1.4734387
|View full text |Cite
|
Sign up to set email alerts
|

Ambient habitat noise and vibration at the Georgia Aquarium

Abstract: Underwater and in-air noise evaluations were completed in performance pool systems at Georgia Aquarium under normal operating conditions and with performance sound tracks playing. Ambient sound pressure levels at in-pool locations, with corresponding vibration measures from life support system (LSS) pumps, were measured in operating configurations, from shut down to full operation. Results indicate noise levels in the low frequency ranges below 100 Hz were the highest produced by the LSS relative to species he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Enrichment components such as wave machines, sprinklers, and bubble machines produce extra environmental noise from machinery and action. The life support systems contribute the most to structure-borne ambient sound with continuous noise produced from pump machinery [ 46 , 47 ]. Results on the decibel and frequency of life support systems have been mixed.…”
Section: Anthropogenic Noise Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enrichment components such as wave machines, sprinklers, and bubble machines produce extra environmental noise from machinery and action. The life support systems contribute the most to structure-borne ambient sound with continuous noise produced from pump machinery [ 46 , 47 ]. Results on the decibel and frequency of life support systems have been mixed.…”
Section: Anthropogenic Noise Pollutionmentioning
confidence: 99%
“…One study found that ambient noise levels in the largest pool of the Monterey Bay Aquarium were 15–25 dB higher than the bay environment that it was simulating, increasing with proximity to the pump room [ 46 ]. More recently, research at the Georgia Aquarium dolphin exhibit found that overall noise levels in-air and underwater were minimally above lower hearing thresholds of bottlenose dolphins, Tursiops truncatus , and the fully operational (all pumps running) life support systems raised ambient noise levels by approximately 10 dB primarily in frequencies under 1000 Hz [ 47 ]. Ambient noise levels above 1000 Hz were not significantly different, with the life support machinery completely on or off, and ambient noise levels of 15,000 kHz near the bottlenose dolphins’ most sensitive hearing range exhibited no marked impact due to life support systems [ 47 ].…”
Section: Anthropogenic Noise Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoos and aquariums often claim that marine mammals are not bothered by in-air noise (see, e.g., Scheifele et al 2012, which measured in-air sound levels at Georgia Aquarium but discussed the results only in terms of what was audible underwater). 77 This argument assumes that captive marine mammals spend most of their time below the water's surface.…”
Section: Noisementioning
confidence: 99%
“…16 However, there is, in fact, a considerable and growing body of published peer-reviewed literature that is relevant to the various regulations in question, notably the requirements for space, temperature, lighting, and water quality, as well as regarding health and disease issues and noise. 17 Several studies (e.g., Ugaz et al 2009;Scheifele et al 2012;Clark 2013) have noted the paucity of research on the welfare of captive marine mammals, particularly cetaceans. Unlike many other species, whether terrestrial wildlife or domesticated animals (see, e.g., Morgan and Tromborg 2007;Whitham and Wielebnowski 2013;Hartstone-Rose et al 2014), captive marine mammals, especially cetaceans, have only rarely been subjects of welfare or non-husbandry-related research (Hill and Lackups 2010;Hill et al 2016).…”
mentioning
confidence: 99%